Investigation of Plasma Immersion Ion Implantation Process in Magnetic Mirror Geometry - de Dios Mitma Pillaca, Elver Juan [UNESP]; Ueda, Mario; Kostov, Konstantin Georgiev [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Plasma immersion ion implantation (PIII) with low external magnetic field has been investigated both numerically and experimentally. The static magnetic field considered is essentially nonuniform and is generated by two magnetic coils installed outside the vacuum chamber. Experiments have been conducted to investigate the effect of two of the most important PIII parameters: target voltage and gas pressure. In that context, it was found that the current density increased when the external parameters were varied. Later, the PIII process was analyzed numerically using the 2.5-D computer code KARAT. The numerical results show that the system of crossed E x B fields enhances the PIII process. The simulation showed an increase of the plasma density around the target under the operating and design conditions considered. Consequently, an increase of the ion current density on the target was observed. All these results are explained through the mechanism of gas ionization by collisions with electrons drifting in crossed E x B fields.
Keywords: Ion implantation; magnetic confinement; magnetic mirror; plasma immersion ion implantation (PIII)